Dietary tofu intake and long-term risk of death from stroke in a general population. Issue 1 (February 2018) - Nguyen, Ho N.; Miyagawa, Naoko; Miura, Katsuyuki; Okuda, Nagako; Yoshita, Katsushi; Arai, Yusuke; Nakagawa, Hideaki; Sakata, Kiyomi; Ojima, Toshiyuki; Kadota, Aya; Takashima, Naoyuki; Fujiyoshi, Akira; et al.
Summary: Background & aim: Although dietary soy intake is linked with health benefits, a relation with stroke has not been established. The present study examined the association between the intake of tofu, the richest source of dietary soy, with stroke mortality in a general population cohort of Japanese men and women. Methods: Data comprise 9244 Japanese enrolled in the National Nutrition Survey of Japan in 1980. Participants were free of cardiovascular disease and followed for 24 years. Dietary intake was estimated from 3-day weighed food records. Multivariable Cox regression models were used to estimate hazard ratios across levels of tofu intake. Results: During follow-up, there were 417 deaths due to stroke (88 cerebral hemorrhage [CH], 245 cerebral infarction [CI], and 84 of other subtypes). Among all men, and in women aged 65 years or more, tofu intake was unrelated to each form of stroke. For young women (<65 years of age), a significantly lower risk of CH in the top versus bottom quartile of tofu intake was observed (Multivariable-adjusted HR = 0.26, 95% CI: 0.08–0.85). Conclusions: In this large prospective study with long follow-up of Japanese men and women, consumption of tofu was unrelated to the risk of stroke except for CH in women <65 years of age. Whether the association in younger women is real or due to chance alone warrants further study.